Choose the answer based on the most efficient method as presented in the lesson.
If the first step in the solution of the equation 2x - 8 = 5x + 3 is "subtract 2x," then what should the next step be?

Respuesta :

subtract 3 from both sides to get
-11=3x

Remember that to solve an equation we need to isolate the variable in one side. To do it we can perform any mathematical operations we want as long as we perform the operations to both sides of the equation.

Let's solve our equation step by step

Step 1. Subtract [tex] 2x [/tex] from both sides of the equation

[tex] 2x-8=5x+3 [/tex]

[tex] 2x-2x-8=5x-2x+3 [/tex]

[tex] -8=3x+3 [/tex]

Step 2. Subtract 3 from both sides of the equation

[tex] -8-3=3x+3-3 [/tex]

[tex] -11=3x [/tex]

Step 3. Divide both sides of the equation by [tex] 3 [/tex]

[tex] -11=3x [/tex]

[tex] \frac{-11}{3} =\frac{3x}{3} [/tex]

[tex] -\frac{11}{3} =x [/tex]

[tex] x=-\frac{11}{3} [/tex]

We can conclude that the next step is: subtract 3 from both sides of the equation.